Therapeutic Potential of Stem Cells Strategy for Cardiovascular Diseases - Chang Youn Lee; Ran Kim; Onju Ham; Jihyun Lee; Pilseog Kim; Seokyeon Lee; Sekyung Oh; Hojin Lee; Minyoung Lee; Jongmin Kim; Woochul Chang (Stem Cells International)
Despite development of medicine, cardiovascular diseases (CVDs) are still the leading cause of mortality and morbidity worldwide. Over the past 10 years, various stem cells have been utilized in therapeutic strategies for the treatment of CVDs. CVDs are characterized by a broad range of pathological reactions including inflammation, necrosis, hyperplasia, and hypertrophy. However, the causes of CVDs are still unclear. While there is a limit to the currently available target-dependent treatments, the therapeutic potential of stem cells is very attractive for the treatment of CVDs because of their paracrine effects, anti-inflammatory activity, and immunomodulatory capacity. Various studies have recently reported increased therapeutic potential of transplantation of microRNA- (miRNA-) overexpressing stem cells or small-molecule-treated cells. In addition to treatment with drugs or overexpressed miRNA in stem cells, stem cell-derived extracellular vesicles also have therapeutic potential because they can deliver the stem cell-specific RNA and protein into the host cell, thereby improving cell viability. Here, we reported the state of stem cell-based therapy for the treatment of CVDs and the potential for cell-free based therapy.